Gabrielle Marceau and WTO Dispute Settlement Rules of Conduct - Davey, William (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2025)
This article honors Gabrielle Marceau’s notable career at the World Trade Organization (WTO) and her role in developing international economic law, the WTO’s dispute settlement system and the innovative rules she helped establish for the WTO’s Dispute Settlement Understanding (DSU). The paper discusses the practical application of the Rules of Conduct, noting that they have generally been effective in maintaining the integrity of the dispute settlement system. Issues related to the ethical behavior of lawyers, and the potential establishment of a WTO Bar Association are also considered. Overall, the Rules of Conduct have successfully addressed ethical concerns and contributed to the credibility of the WTO dispute settlement system.